Modelling Effects of Tariff Liberalisation on India's Key Export Sectors: Analysis of the EU–India Free Trade Agreement. (February 2017) - Khorana, Sangeeta; Narayanan, Badri G.
Trade agreements are increasingly being negotiated between developed and emerging economy partners. An example is the EU–India Free Trade Agreement (FTA) for which negotiations began in 2007. There has been a debate on the potential effects of the proposed FTA and how this can impact on India's key export sectors. Our study addresses this aspect from a global computable general equilibrium (CGE) modelling perspective. Using the Global Trade Analysis Project (GTAP) framework, we analyse trade and welfare impacts of the proposed FTA between the EU and India. Two scenarios are modelled: first, complete and immediate elimination of tariff on all goods traded and second, selective tariff elimination on textiles, wearing apparel and leather goods—products in which India has a comparative advantage. Results under both scenarios show that India enjoys positive welfare effects though there is a possibility of trade diversion. Under scenario 1, India loses due to a negative terms of trade (ToT) effect. Under scenario 2, with selective sectoral liberalisation, gains are mainly concentrated in the textiles, wearing apparel and leather sectors. There is a positive output effect from change in demand for factors of production, suggesting that the proposed FTA could lead to relocation of labour-intensive production to India. JEL Classification: F15, F47, F62